Design and understanding of a high-performance gas sensing material based on copper oxide nanowires exfoliated from a copper mesh substrate. Issue 41 (29th September 2015) - Yang, Fuchao; Guo, Jie; Liu, Mingming; Yu, Shen; Yan, Ningbo; Li, Jing; Guo, Zhiguang
Abstract : A high-performance gas sensing material based on copper oxide nanowires exfoliated from a Copper Mesh Substrate (CMS). Abstract : We report a novel and facile route to synthesize a 1D needlelike CuO gas sensor utilizing simple solution-treatment, heat-treatment and sonication processes based on copper meshes (CMs) for the first time. We have demonstrated that the architectural 1D CuO sensor displays a substantial improvement of response magnitude toward a series of toxic organic molecules. We expect that our work may provide a new inspiration for synthesizing 1D semiconductor nanowires for gas sensing application.